Probiotic Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 May Help Downregulate TNF-Alpha, IL-6, IL-8, IL-10 and IL-12 (p70) in the Neurogenic Bladder of Spinal Cord Injured Patient with Urinary Tract Infections: A Two-Case Study - Kingsley C. Anukam; Keith Hayes; Kelly Summers; Gregor Reid (Advances in Urology)
The management of urinary tract infection (UTI) in individuals with spinal cord injury (SCI) continues to be of concern, due to complications that can occur. An emerging concept that is a common underlying pathophysiological process is involved, wherein pathogens causing UTI have a role in inflammatory progression. We hypothesized that members of the commensal flora, such as lactobacilli, may counter this reaction through anti-inflammatory mediation. This was assessed in a pilot two-patient study in which probiotic Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri were administered to one patient and placebo to another, both along with antibiotics to treat acute UTI. Urinary TNF-alpha was significantly downregulated (P=.015) in the patient who received the probiotic and who used intermittent catheterization compared with patient on placebo and using an indwelling catheter. The extent to which this alteration resulted in improved well-being in spinal cord injured patients remains to be determined in a larger study.